Phytochemical Fingerprinting and Activity of Premna barbata Wall. ex-Schauer Stem Bark Extract - Monika, Monika; Kumar, Neeraj (Journal of Neonatal Surgery, 2024)
Premna Barbata Wall. Ex Schauer (family Verbenaceae) is found in the jungle provinces of the eastern and northern parts of India, Pakistan, Nepal, and Myanmar, in addition to in tropical and subtropical areas of Asia, Africa, Australia, and the Pacific Islands. It can be found in the lower Himalayas and the Shivalik tract in India. The range of raises is 800–1800 meters. Plant bark is 2 to 5 cm long and 1 to 2 cm wide, with a little quilled shape. The superficial surface is grey, while the inner surface is white. The analysis of the literature divulges that the plant has been the subject of very few actual investigations and studies. The present study is based on an initial phytochemical screening examination and an assessment of the in vitro potential for the inhibition of the enzyme’s alpha-glucosidase and alpha-amylase. The research indicates that the hydro-alcoholic extract comprises a range of phytochemical constituents present in diverse quantities, such as loss on drying (11.4%), total starch (0.92%), total sugar (0.66%), flavonoids (0.24%), tannins (1.24%), phenolic compounds (3.10%), proanthocyanidins (2.18%), and flavonols (0.23%), among others